Circadian influences on central nervous system barriers and the glymphatic system - Elliott, Brittany D.; Kisamore, Claire O.; Nelson, Randy J.; DeVries, A. Courtney; Walker, William H. (Frontiers in Physiology, 2025)
The central nervous system (CNS), comprising the brain and spinal cord, is fortified by complex barriers that protect the underlying organs and maintain homeostasis. The importance of proper fortification and homeostatic regulation provided by these systems has broad implications for many physiological processes and several pathological conditions are associated with their disruption. Recent studies support the notion that CNS barriers and fluids are regulated by circadian rhythms. Whereas reciprocal associations between the structural and functional integrity of neural barriers and disease states are well-established, the role of circadian rhythms in mediating these relationships remains unspecified. The goals of this review are to provide a general overview of three primary systems responsible for maintaining CNS homeostasis, namely the blood-brain barrier, blood-cerebrospinal fluid barrier, and glymphatic system, and to synthesize recent evidence highlighting the role of circadian rhythms as a critical regulator of CNS fluid and barrier function.